1991
DOI: 10.3382/ps.0701790
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-I and Insulin as Growth and Differentiation Factors in Chicken Embryogenesis

Abstract: The avian embryo has been a useful model system for studies on the role of insulin and its close relative insulin-like growth factor-I (IGF-I) in development. The unfertilized chicken egg contains both peptides from maternal origin, and the embryo expresses insulin and IGF-I before the major organs are formed. Insulin receptors and IGF-I receptors are found in the blastoderm and in all tissues examined during organogenesis. When exogenous insulin or IGF-I are added to the embryo, growth and differentiation eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…While liver IGF-I mRNA was very low until the end of embryogenesis, other chicken embryo tissues had significant IGF-I mRNA levels between days 12-18 (9,34). How production of IGF-I in individual organs (pancreas, brain, etc.)…”
Section: Discussionmentioning
confidence: 93%
“…While liver IGF-I mRNA was very low until the end of embryogenesis, other chicken embryo tissues had significant IGF-I mRNA levels between days 12-18 (9,34). How production of IGF-I in individual organs (pancreas, brain, etc.)…”
Section: Discussionmentioning
confidence: 93%
“…Skalkidou et al (2003) also reported that IGF-1 plays a dominant role in pre- and perinatal growth in human. However, most studies supported that IGF-1 played a larger role in neonatal and postnatal growth (Heyner et al, 1990; De Pablo et al, 1991; Baker et al, 1993; Liu et al, 1998). In this study, a progressive increase pattern of IGF-1 level along with porcine growth and development also indicated an important role of IGF-1 for individual growth.…”
Section: Discussionmentioning
confidence: 99%
“…These increased pancreatic insulin levels may contribute to elevated plasma insulin levels with chicken embryonic age, with a high peak on ED 17 followed by plateau during pipping and hatching (Lu et al, 2007). Insulin receptors are also found in the blastoderm and in all chicken tissues during embryogenesis (De Pablo et al, 1991). After binding with insulin during the chicken embryogenesis, both have important roles in developmental events, such as growth (Bassas et al, 1987;De Pablo et al, 1991;Lu et al, 2007;Patwardhan et al, 2004), regulation of protein (Hohlweg et al, 1999) and carbohydrate metabolism (Foltzer et al, 1982;Lu et al, 2007;Parkes and Grieninger, 1985).…”
Section: Embryonic and Neonatal Developmental Changes Of Plasma Insulmentioning
confidence: 96%
“…Insulin receptors are also found in the blastoderm and in all chicken tissues during embryogenesis (De Pablo et al, 1991). After binding with insulin during the chicken embryogenesis, both have important roles in developmental events, such as growth (Bassas et al, 1987;De Pablo et al, 1991;Lu et al, 2007;Patwardhan et al, 2004), regulation of protein (Hohlweg et al, 1999) and carbohydrate metabolism (Foltzer et al, 1982;Lu et al, 2007;Parkes and Grieninger, 1985). After hatch, feed-deprived broiler chickens have plasma insulin concentrations that are approximately 0.1 ng mL -1 and after day (D) 14 posthatch, these levels increased to approximately 0.5 ng mL -1 at D 28.…”
Section: Embryonic and Neonatal Developmental Changes Of Plasma Insulmentioning
confidence: 97%